Semarang’s nature tourism: Sustaining growth through digital-based innovation and stakeholder collaboration - Perdana, Putra; Riyadi, Bambang; Yuliari, Giyah (Journal of Sustainable Tourism and Entrepreneurship, 2025)
Purpose: This study aims to explore strategies for conserving sustainable nature tourism in Semarang City by emphasizing the roles of stakeholder collaboration and digital-based innovation. As a provincial capital, Semarang holds diverse yet under-optimized tourism potential, especially in its natural attractions. Methodology/approach: The research uses a qualitative case study approach focusing on Tinjomoyo Forest and Jatibarang Reservoir. Data were gathered through in-depth interviews with stakeholders, participant observation, and document analysis. Thematic analysis was applied to identify patterns related to collaboration and digital transformation in tourism management. Results/findings: Findings show that collaboration among local governments, MSMEs, and communities has supported improvements in tourism services and promotion. However, the adoption of digital technologies for governance and marketing remains limited. Infrastructure deficits and lack of digital capacity are key barriers Conclusion: Strengthening stakeholder collaboration, enhancing digital literacy, and developing inclusive infrastructure are critical to advancing sustainable tourism in Semarang. A practical development model integrating community empowerment and technology is essential for long-term impact.equipment, reducing reliance on conventional UPS systems. Limitations: This study is limited to two tourism sites and relies solely on qualitative methods, reducing its generalizability. Contribution: This research contributes to the discourse on urban sustainable tourism by offering a replicable model centered on collaboration and digital innovation, particularly applicable to developing cities facing rapid urbanization and environmental challenges.